The mediating role of international student satisfaction in the influence of higher education service quality on institutional reputation in Taiwan. (7th December 2020) - Moslehpour, Massoud; Chau, Ka Yin; Zheng, JingJing; Hanjani, Asalia Noor; Hoang, Minh
The number of international students applying to universities in Taiwan is increasing annually. Moreover, universities' choice for international students is also increasing with support from the Ministry of Education of Taiwan. Therefore, it is crucial to understand the factors that influence student choice. This study investigates the effects of Taiwan's higher education service quality on international student satisfaction and institutional reputation. We collected data from 197 international students studying at 33 national and private universities in Taiwan to test the study's proposed model. This study uses a quantitative approach to examine the proposed hypotheses, and causal research design is used to elucidate the cause-and-effect relationship between constructs. The non-academic aspect of service quality is the most influential variable in student satisfaction, and student satisfaction strongly affects institutional reputation. Student satisfaction mediates the relationship between the academic and non-academic aspects of service quality and institutional reputation. This study's findings could help higher education institutions in Taiwan assess and improve their service quality, which would help them attract international students.